Dicentrine Purified from the Leaves of Ocotea puberula Controls the Intracellular Spread of L. (L.) amazonensis and L. (V.) braziliensis Amastigotes and Has Therapeutic Activity as a Topical Treatment in Experimental Cutaneous Leishmaniasis - Jesus, Jéssica Adriana [UNESP]; Flores, Gabriela Venicia Araujo [UNESP]; da Silva Souza, Dalete Christine; Tristão, Daniela Costa; Serrano, Dolores Remedios; Lalatsa, Aikaterina; Laurenti, Márcia Dalastra; Lago, João Henrique Ghilardi; Ferraz, Humberto Gomes; da Silva, Rosana Pereira; Passero, Luiz Felipe Domingues [UNESP] (MDPI, 2025)
Leishmaniasis, a complex disease caused by protozoal parasites of the genus Leishmania, presents various clinical forms, particularly a cutaneous clinical form. Treatment is typically performed with pentavalent antimonial and amphotericin B, both of which have severe side effects that hinder patient compliance. This emphasizes the need for the development of new, effective, and safe treatments. In this study, the leishmanicidal activity of the methanolic extract, an alkaloid-enriched fraction and dicentrine, the main alkaloid of the leaves of Ocotea puberula (Lauraceae), a native Brazilian plant traditionally used by the indigenous population to treat skin affections, was investigated in vitro. Additionally, an in vivo study evaluated the efficacy of a topical cream containing 0.5% dicentrine. The in vitro studies demonstrated high activity and selectivity of methanolic extract, alkaloid-enriched fraction, and dicentrine against the promastigote and amastigote forms of Leishmania (Leishmnia) amazonensis and Leishmania (Viannia) braziliensis. The leishmanicidal effect of dicentrine was related to the modulation of macrophage microbicidal activity. A cream containing 0.5% dicentrine showed high stability and, in permeation studies, dicentrine was retained in a skin-mimicking artificial membrane. This cream effectively inhibited the progression of the skin lesion in BALB/c mice infected with L. (L.) amazonensis, together with a reduced parasite number. Thus, dicentrine offers a promising alternative to the treatment of skin leishmaniasis.